The Origin of Ekman Flow in a Cavity Subject to Impulsive Rotational Motions - Wen-Jei Yang; Hiroshi Ohue; Genshi Kawashima (International Journal of Rotating Machinery)
An experimental study is performed to disclose the origin of Ekman flow on the surfaces of a rotating drum resulting from fluid-structure interaction after an impulsive start of motion (referred to as the spin-up process) or an impulsive stop (the spin-down process). Laser Doppler velocimetry (LDV) is employed to determine instantaneous distribution of both the radial and angular velocity components in the flow field inside the rotating drum. From these results, the secondary flow and the time history of the Ekman boundary layer thickness are determined. The tracer/light sheet method is also engaged to enable real-time visualization of flow patterns. Fluid viscosity, drum size and rotational speed are varied to determine their effects on fluid-structure interactions. Results may be applied to cavity flow in rotating machinery.